Satellite Navigation of a Lunar Rover with Sensor Fusion for High-Accuracy Navigation - Marco Sabatini; Giovanni B. Palmerini; Filippo Rodriguez; Riccardo Petix; Gabriele Lambiase; Pietro Pacchiarotti (Aerospace, 2025)
The Moon has become the focus of renewed interest for numerous space agencies and private companies worldwide. In the coming years, various scientific and commercial missions are planned, with a particular emphasis on exploring the South Pole. These missions include orbiters, landers, as well as both static and mobile rovers. For all these operations, continuous and accurate position knowledge is essential. This paper evaluates the performance of a navigation system designed for a lunar rover using the future satellite navigation infrastructure. It highlights the critical role of integrating multiple information sources, including a Digital Elevation Model (DEM) of the lunar surface and a high-precision Inertial Measurement Unit (IMU). The results demonstrate that a comprehensive suite of instruments enables highly accurate and reliable navigation for a mobile rover. While standalone satellite navigation, due to the reduced number of available sources, offers navigation accuracy of the orders of tens of meters, the addition of the DEM lowers the error at 5 m level; the IMU further improve by roughly 40% the performance on horizontal positioning.